2005
DOI: 10.1158/1078-0432.ccr-04-2172
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Immunization with Dendritic Cells Modified with Fowlpox Encoding Carcinoembryonic Antigen and Costimulatory Molecules

Abstract: Purpose:To determine the safety and immunologic and clinical efficacy of a dendritic cell vaccine modified to hyperexpress costimulatory molecules and tumor antigen. Experimental Design: In this phase I study, we administered one or two cycles of four triweekly s.c./intradermal injections of ex vivo generated dendritic cells modified with a recombinant fowlpox vector encoding carcinoembryonic antigen (CEA) and a triad of costimulatory molecules [rF-CEA(6D)-TRICOM]. Controls consisted of immature dendritic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 17 publications
0
56
0
Order By: Relevance
“…Briefly, cytomegalovirus-driven LacZ (originally described in reference 19) and human carcinoembryonic antigen (CEA) (described in reference 44,31) were independently subcloned into shuttle plasmids and used to generate [E1-E3-] and [E1-E2b-E3-] vectors using a previously described, bacterial-recombination-based system (20). Complementing C-7 cell lines (containing the Ad E2 polymerase and pTP genes) were used to produce high-titer stocks of these vectors, and cesium chloride double banding was performed to purify the vectors, as previously detailed (3).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, cytomegalovirus-driven LacZ (originally described in reference 19) and human carcinoembryonic antigen (CEA) (described in reference 44,31) were independently subcloned into shuttle plasmids and used to generate [E1-E3-] and [E1-E2b-E3-] vectors using a previously described, bacterial-recombination-based system (20). Complementing C-7 cell lines (containing the Ad E2 polymerase and pTP genes) were used to produce high-titer stocks of these vectors, and cesium chloride double banding was performed to purify the vectors, as previously detailed (3).…”
Section: Methodsmentioning
confidence: 99%
“…It has been proposed that a superior malaria vaccine will be multistage and multi-component requiring a high capacity vector such as MVA [50]. Using dendritic cells infected with poxvirus encoding CEA and co-stimulatory molecules B7-1, ICAM-1 and LFA-3 activates potent CEA-specific immune responses [51]. Recent clinical studies indicated that MVA expressing HIV-1 Gag coupled to other CD8+ T-cell epitopes could induce multifunctional HIV-1-specific T cells in healthy subjects or in individuals with chronic HIV-1 infection [13,52].…”
Section: Discussionmentioning
confidence: 99%
“…Phase I clinical trials using the CEA loaded MDDCs in colorectal cancer patients indicated that they induced both a CD4+ and CD8+ effector response, but that T suppressor activity may have impacted on the full effect of the vaccine [67]. MDDCs loaded with CEA and melanoma associated antigen 3 (MAGE-3) induced significant increases in the killing of target cells by CTLs [68].…”
Section: Figure 2 Il-4 and Gm Csf Differentiates Human Monocytes Intmentioning
confidence: 99%